Childcare Facilities, Availability of Substitute Workers and Parental Leave Utilization - 김정호 (Korea and the World Economy, 2018)
This study investigates to what extent parental leave (PL) utilization is influenced by two kinds of social infrastructure. The analysis based on National Employment Insurance database finds that 10%p increase in the availability of local childcare facilities raises the PL take-up by 1%p and its duration by five days and that 1%p rise in the female unemployment rate increases the take-up by 0.2%p and its duration by one day. These results suggest that an increase in the access to childcare service and in the availability of substitute workers promotes utilization of PL.
Keywords: parental leave; female labor supply; childcare facility; substitute workers; local labor market